Screening Approach for Chiral Separation of β‐Aminoketones by HPLC on Various Polysaccharide‐Based Chiral Stationary Phases. Issue 5 (6th March 2015) - Addadi, Khadidja; Sekkoum, Khaled; Belboukhari, Nasser; Cheriti, Abdelkrim; Aboul‐Enein, Hassan Y.
Abstract Nine β‐aminoketones were synthesized via Mannich reaction when benzaldehyde was condensed with some primary amines and acetophenone. The purified compounds were identified by using spectroscopic methods. The enantiomeric separation of these derivatives was carried out by high‐performance liquid chromatography (HPLC) using several coated and immobilized polysaccharide stationary phases, namely, Chiralcel® OD‐H, Chiralcel® OD, Chiralcel® OJ, Chiralpak® AD, Chiralpak® IA, and Chiralpak® IB using different mobile phases composed of n‐hexane and alcohol mixed in various ratios or pure ethanol or isopropanol. The retention behavior and selectivity of these chiral stationary phases were examined in isocratic normal phase mode. The results indicate that cellulose derivatives have higher enantioselectivity than amylose derivatives for the separation of racemic β‐amino ketones. Chirality 27:332–338, 2015. © 2015 Wiley Periodicals, Inc.